Toxic Effects of Zinc Chloride on the Bone Development in Danio rerio (Hamilton, 1822) - Salvaggio, Antonio; Marino, Fabio; Albano, Marco; Pecoraro, Roberta; Camiolo, Giuseppina; Tibullo, Daniele; Bramanti, Vincenzo; Lombardo, Bianca M.; Saccone, Salvatore; Mazzei, Veronica; Brundo, Maria V. (Frontiers in Physiology, 2016)
The increase of heavy metals in the environment involves a high exposure of aquatic organisms to these pollutants. The present study is planned to investigate the effects of zinc chloride (ZnCl2) on the bone embryonic development of Danio rerio and confirm the use of zebrafish as a model organism to study the teratogenic potential of this pollutant. zebrafish embryos were exposed to different ZnCl2 concentrations and analyzed by ICP-MS. The skeletal anomalies were evaluated to confocal microscope after staining with calcein solution and RhodZinTM-3,AM. The data show a delay in hatching compared with the controls, malformations in the process of calcification and significant defects in growth. In conclusion, the current work demonstrates for the first time the Zn toxic effects on calcification process and confirm zebrafish (Danio rerio) as suitable alternative vertebrate model to study the causes and the mechanisms of the skeletal malformations.